Functions and clinical significance of circular RNAs in glioma - Jikui Sun (Molecular Cancer, 2020)
Abstract CircRNAs are a class of single-stranded RNA molecules with a covalently closed loop structure and have been characterized by high stability, abundance, conservation, and display tissue/developmental stage-specific expression, furthermore, based on the abundance in distinct body fluids or exosomes, circRNAs present novel biomarkers and targets for the diagnosis and prognosis of cancers. Recently, the regulatory mechanisms of biogenesis and molecular functions, including miRNAs and RBPs sponge, translation as well as transcriptional and splicing regulation, have been gradually uncovered, although various aspects remained to be elucidated in combination with deep-sequence and bioinformatics. Accumulating studies have indicated that circRNAs are more enriched in neuronal tissues partly due to the abundance of specific genes promoting circularization, suggesting dysregulation of circRNAs is closely related to diseases of the nervous system, including glioma. In this review, we elaborate on the biogenesis, functions, databases as well as novel advances especially involved in the molecular pathways, highlight its great value as diagnostic or therapeutic targets in glioma.